Recombinant Human Adenovirus Type 5 Co-expressing RABV G and SFTSV Gn Induces Protective Immunity Against Rabies Virus and Severe Fever With Thrombocytopenia Syndrome Virus in Mice - Zhao, Zhongxin; Zheng, Wenwen; Yan, Lina; Sun, Peilu; Xu, Tong; Zhu, Yelei; Liu, Lele; Tian, Li; He, Hongbin; Wei, Yurong; Zheng, Xuexing (Frontiers in Microbiology, 2020)
Both severe fever with thrombocytopenia syndrome (SFTS) and rabies are severe zoonotic diseases. As co-hosts of rabies virus (RABV) and SFTS virus (SFTSV), dogs and cats could not only be infected, but also transmit the virus to human. Hence, developing a bivalent vaccine against both SFTS and rabies is urgently needed. In this study, we generated a recombinant replication-deficient human adenovirus type 5 (Ad5) co-expressing RABV G and SFTSV Gn (Ad5-G-Gn) and evaluated its immunogenicity and efficacy in mice. Ad5-G-Gn immunization activated more Dendritic cells (DCs) and B cells in lymph nodes, and induced Th1-/Th2-mediated responses in splenocytes, leading to robust production of neutralizing antibodies against SFTSV and RABV. In addition, single dose of Ad5-G-Gn conferred mice complete protection against lethal RABV challenge and significantly reduced splenic SFTS viral load. Therefore, our data support further development of Ad5-G-Gn as a potential bivalent vaccine candidate against SFTS and rabies for dog and cat use.